Non-invasive brain stimulation in research and therapy - Pushpal Desarkar; Carmelo Mario Vicario; Mojtaba Soltanlou (Scientific Reports)
Abstract Since the introduction of transcranial magnetic stimulation (TMS) almost four decades ago, non-invasive brain stimulation (NIBS) techniques have emerged as promising tools to study brain-behaviour relationships in healthy and impaired states with unprecedented precision. Various NIBS techniques, including TMS, transcranial direct current stimulation (tDCS), and emerging methods such as transcranial alternating current stimulation (tACS) and transcranial random noise stimulation (tRNS) are employed in both research and clinical settings. TMS has gained regulatory approval for treating conditions like major depressive disorder and migraine, while tDCS is showing efficacy in enhancing cognitive functions in various populations. This collection of articles examines key studies, including the modulation of cognitive-motor functions, optimization of light stimulation for Alzheimer’s therapy, and effects on risk-taking behaviour in violent offenders. Notably, the findings suggest that NIBS can effectively influence executive functions and decision-making processes. They highlight the integration of NIBS with neuroimaging techniques, the importance of personalized targeting, and the potential for combined therapeutic approaches. Future directions include addressing methodological challenges and leveraging artificial intelligence to refine treatment protocols. Collectively, these advancements position NIBS as a transformative tool in both neuroscience research and clinical practice, offering new avenues for understanding and treating complex neuropsychiatric conditions.